Influence of coir random fibre length on concrete: mechanical properties - Misnon, Noor Aina; Che Osmi, Siti Khadijah; Shahidan, Shahiron; Chouw, N. (CREAM-CIDB, 2017)
Incorporating coconut fibre in construction materials is gaining more interest nowadays, mainly due to its toughness and environmental friendliness. Previous studies on the development of Coconut Fibre Reinforced Concrete (CFRC) have revealed that an addition of coconut fibres can significantly enhance both the static and dynamic properties of CFRC composite. However, the studies focused on the influence of fixed fibre length. The fixed length fibres involve additional preparation and thus requires additional cost. To reduce the production cost, random length of fibres is considered. This research paper is mainly emphasized on the influence of random length fibres in CFRC. Four different fibres contents were added to the concrete; 1%, 2%, 3% and 5% of the cement weight. The cement, sand and aggregate ratio used was 1:2:2, with water cement ratio in the range of 0.48 to 0.65. A number of experiments on CFRC with random fibre length were conducted to identify the static properties of CFRC composite, i.e. compressive strength, splitting tensile strength, modulus of elasticity and flexural strength. The results revealed the mechanical characteristics are similar to that of CFRC with fixed lengths.